Diversity and distribution bromeliads plants as breeding habitat for mosquito larvae (Diptera: Culicidae) in Bogor, Indonesia - M Ikhsan; UPIK KESUMAWATI HADI; SUSI SOVIANA (Society for Indonesian Biodiversity, 2020)
Abstract. Ikhsan M, Hadi UK, Soviana S. 2020. Diversity and distribution bromeliads plants as breeding habitat for mosquito larvae (Diptera: Culicidae) in Bogor, Indonesia. Biodiversitas 21: 3494-3498. Bromeliads leaf structure can hold water and has potential as the breeding ground for mosquitoes. Information regarding the potential of bromeliads as a habitat for mosquito larvae in Indonesia is limited. This study aims to identify the diversity of bromeliads and their potential as breeding habitat for mosquito larvae in West Bogor Sub-district, Bogor City, West Java, Indonesia. Determination of the sample using purposive sampling method. Larvae collections were carried out on bromeliads that were outside the building in December 2019 to Maret 2020. The collection used a 50 ml syringe that was modified using a small pipe. Total bromeliads collected were 117 consisted of Neoregelia, Cryptanthus, dan Alcantarea from 50 observation points. The percentage of mosquito larvae presence from bromeliads was 74.4%. Total larvae collected were 859 larvae consisting of Aedes albopictus, Aedes aegypti, Aedes spp., Armigeres subalbatus, and Culex quinquefasciatus. The diversity of mosquito larvae found in the bromeliads were low (H'=0.16), while the dominant species of mosquito larvae were Ae. albopictus (61.55%) and confirmed as the second vector of Dengue Fever in Indonesia. The results of this study indicate that bromeliads have potential as a breeding site for mosquito larvae in West Bogor Sub-district, Bogor City.